OVERDOSE RISK AND ACQUIRING OPIOIDS FOR NONMEDICAL USE EXCLUSIVELY FROM PHYSICIANS IN VANCOUVER, CANADA - Cheng, Tessa (Subst Use Misuse, 2020)
BACKGROUND: A primary response to the alarming rise in overdose and mortality due to nonmedical prescription opioid (PO) use has been to restrict opioid prescribing; however, little is known about the relationship between obtaining opioids from a physician and overdose risk among people who use POs nonmedically and illicit street drugs. OBJECTIVES: Investigate the relationship between non-fatal overdose and acquiring POs exclusively from physicians for the purposes of engaging in nonmedical PO use. METHODS: Data were collected between 2013 and 2016 among participants in two harmonized prospective cohort studies of people who use drugs in Vancouver: the At-Risk Youth Study (ARYS) and the Vancouver Injection Drug Users Study (VIDUS). Analyses were restricted to participants who engaged in nonmedical PO use and used generalized estimating equations. RESULTS: Among 599 participants who used POs nonmedically, 82 (14%) individuals reported acquiring POs exclusively from a physician and 197 (33%) experienced a non-fatal overdose at some point over the study period. Acquiring POs exclusively from physicians was significantly and negatively associated with non-fatal overdose in the bivariate analysis (Odds Ratio=0.60, 95% Confidence Interval (CI): 0.39–0.94) but not the final multivariate analysis (Adjusted Odds Ratio =0.87, 95% CI: 0.53–1.44). CONCLUSIONS: Compared to individuals who acquired POs from friends or the streets, participants who acquired POs exclusively from a physician were not at an increased risk of non-fatal overdose. Although responsible opioid prescribing is an important priority, additional strategies to address nonmedical PO use are urgently needed to reduce overdose and related morbidity and mortality.